THE SURVEY OF TEACHERS’ ATTITUDE TOWARDS THE EVALUATION OF 21ST CENTURY SKILLS FOR THAI STUDENTS - Junpho, Meechai (PEOPLE: International Journal of Social Sciences, 2015)
This research is surveying on teachers’ attitude towards the evaluation of 21st century skills for Thai Students by conducting the brainstorming session on the evaluation of 21st skills, which is learners-centered and public hearing with the samples of 100 teachers and executives from the national network of teachers who use the Quality Learning Foundation’s tools for 21st Century skills and got the best teacher award given to only 20,000 teachers in the country. The survey focuses on the issues of, firstly, types of measurement and evaluation being used at the present, secondly, the suggested types and means of measurement and evaluation of 21st century skills and finally, the problems and Obstacles in measurement and evaluation of 21st century skills. The results of the survey on ‘how the evaluation and measurement of 21st century skills which emphasizes the learner-centered should be’ are; for standard and indicator topic, teachers should measure from letting the learners do the real tasks, explain the measurement standard and objectives in advance and understand the goal of 21st century skills as well as adapting the standards depending on each context. For the measurement and evaluation, the suggested ones are rubric assessment, 360-degree assessment to evaluate the individual development and the learning skills. Also, the aim of measurement and evaluation should be to support the learners learning. Finally, the problems and obstacles of the evaluation of 21st century skills are the lack of proper measurement, the uncovered tests as teachers are from different fields, ONET, the lack of children’ attention, the lack of evaluation teachers, the teachers’ ego, the limitation of school and the policy, the support from the community surroundings, the parents’ attitude of ‘children must be intelligent’, the uncovered evaluation methods and the uncertain period of success and the individual difference.